Every good gift [large type] - Irvin, Kelly (Irvin, Kelly. Amish blessings, 2023)
"During the most difficult season of her life, how could she know whether their meeting was a gift from God--or another temptation? Maisy never expected that a Plain girl like her could have her heart stolen by an Englisch boy. But when her rumspringa ends and Maisy realizes she's pregnant, the reality of their choices--and their differences--sets in. Maisy knows she will never leave her faith to marry her baby's father. But she also knows the road to acceptance as an unwed mother in an Amish community will be long and hard. To protect her family from the scandal, she goes to live with her cousin in Haven, Kansas, where she will have some solitude to figure out what kind of future she might have. In Haven Maisy begins to find her way--thanks in no small part to Joshua Lapp, a Plain man who's made it clear he isn't bothered by her situation or ashamed to be seen with her, despite the bishop's warnings. But Joshua has struggled with his faith ever since the death of his twin brother, leaving Maisy to wonder: How can two people who are so lost ever help each other discover Gott's plans for their future?"--